Analisis Persepsi Etika dan Tanggung Jawab Sosial Akuntan Publik dalam Praktik Audit di Era Digitalisasi Keuangan - Dewi, Milatina Laksmita Dewi; Belananda, Maulia Regita Belananda (ICON Publisher, 2025)
This study explores the evolving role of moral reasoning in shaping the ethical orientation of professional accountants within Indonesia’s rapidly digitalizing audit landscape. Using a qualitative phenomenological approach, the research uncovers how digital transformation reshapes ethical awareness, accountability, and social responsibility in the auditing profession. The findings reveal that moral reasoning remains the ethical foundation of auditing, serving as a stabilizing force amid technological disruptions such as automation and artificial intelligence. Ethical integrity, rather than being eroded, adapts through reflective judgment that harmonizes digital competence with professional values. The study further finds that social responsibility and accountability have expanded beyond financial domains to encompass environmental and societal dimensions, redefining the auditor’s role as a moral intermediary between organizations and the public. However, institutional pressures, algorithmic bias, and data privacy challenges continue to test professional autonomy. The research contributes theoretically by integrating professional ethics theory and stakeholder theory, emphasizing that sustainable ethics in auditing depend on moral resilience and human-centered technological governance. Practically, it calls for digital ethics integration in accounting education, ethical mentorship within firms, and policy frameworks such as a Digital Ethical Audit Charter to strengthen integrity in the digital era.